Urgency of Traffic Implementation Regulations against Violations Committed by Foreign Citizens - Dantes, Komang Febrinayanti (PT. Riset Press International, 2023)
Bali tourism has surged again since the government made the decision to reopen the tourism sector in order to encourage activity and economic recovery. Tourism is the mainstay sector of Bali’s economy. Tourist visits to Bali shot up sharply to more than hundreds of visits every week. This raises problems for Bali tourism in the future, especially in the transportation and accommodation sector, because to support daily activities and reduce vacation costs, foreign tourists prefer to rent motorized vehicles freely without showing an international driving license that must be owned by foreign citizens to be able to rent a motorized vehicle in Bali. This is of course an advantage for motor vehicle rental business actors, but on the other hand, traffic violations by foreign nationals have increased, even from minor violations to violations that result in the loss of a person's life. This study uses normative legal research methods with a statue approach, to find a rule, principle, or legal doctrine to answer the legal problems faced.